Peculiarities of using the inductance in the triggering circuit of the LTD switch; Energy Fluxes and Radiation Effects (EFRE-2016) - Alekseenko V. M. Vitaly Mikhaylovich; Sinebryukhov V. A. Vadim; Volkov S. N. Sergei; Kondratiev S. S. Sergei; Kim A. A. Aleksandr (2016, 2016)
Title screen